ITH: an open database on Italian Tenders 2016–2023 - Roberto Nai; Emilio Sulis; Rosa Meo (Scientific Data)
Abstract Governments procure large amounts of goods and services to help them implement policies and deliver public services; in Italy, this is an essential sector, corresponding to about 12% of the gross domestic product. Data are increasingly recorded in public repositories, although they are often divided into multiple sources and not immediately available for consultation. This paper provides a description and analysis of an effort to collect and arrange a legal public administration database. The main source of interest involves the National Anti-Corruption Authority in Italy, which describes more than 3 million tenders. To improve usability, the database is integrated with two other relevant data sources concerning information on public entities and territorial units for statistical purposes. The period identified by domain experts covers 2016–2023. The analysis also identifies key challenges that arise from the current Open Data catalogue, particularly in terms of data completeness. A practical application is described with an example of use. The final dataset, called Italian Tender Hub (ITH), is available in a repository with a description of its use.